A TALE OF TWO ORTHOSES: WHAT FACTORS ENFORCED THE DECISION? - T. Thong; S. Rajasegaran (Asian Journal of Medicine & Health Sciences, 2021)
The increase in foot plantar pressure causes chronic diabetic foot ulcers, which are prone to infection to undergo a slow healing process and would eventually lead to severe consequences. Many methods were proposed to relieve pressure and promote successful wound healing. The objective of this clinical case report is to justify the selection of patellar tendon bearing ankle-foot orthosis (PTB AFO) over the Aircast XP diabetic walker. A 45-year-old lady with underlying diabetes mellitus, morbid obesity and stroke, presented with Charcot foot arthropathy. Features of this case are discussed together with the suitability of different orthoses which are available in Malaysia. Due to the complexity of the patient’s problems, it is challenging to decide the most suitable orthosis for this patient. In conclusion, the treatment plan was to prescribe PTB AFO as it meets the functional and social requirements of the patient compared to Aircast XP diabetic walker.